MODERN INSTRUMENTAL METHODS FOR QUALITATIVE AND QUANTITATIVE ANALYSIS OF LAPATINIB IN BIOLOGICAL FLUIDS AND DOSAGE FORMS (REVIEW) - SHPRAKH, ZOYA S.; POSKEDOVA, YANA A.; RAMENSKAYA, GALINA V. (International Journal of Applied Pharmaceutics, 2022)
Lapatinib is a small molecule, a heterocyclic quinazoline derivative. The drug is used for targeted therapy of patients with breast cancer, in which there is overexpression of the human epidermal growth factor receptors (HER/ErbB). This review is devoted to studying modern instrumental methods of qualitative and quantitative analysis of lapatinib, which can be used both for quality control and standardization (of bulk pharmaceuticals and dosage forms) and pharmacokinetics studies of a drug. Reverse-phase high-performance liquid chromatography (RP-HPLC) is mainly used to identify lapatinib in tablets. Depending on the purpose of the study, various detectors are used (ultraviolet or diode-matrix detector), which makes it possible to determine not only the native compound but also the products of its degradation. Definition of lapatinib in the presence of degraded products is necessary for forced degradation studies to determine drug stability. When a drug is being developed, it is important to define and understand its pharmacokinetics. For such studies, high-performance liquid chromatography (HPLC) coupled with the mass selective detector is often used. It allows determining lapatinib in biological fluids. However, these methods are not applicable for identifying the drug directly in dosage forms and require further development and validation.